Major histocompatibility complex non-restricted presentation to CD4+ T lymphocytes of Mycobacterium leprae heat-shock protein 65 antigen by macrophages transfected with the mycobacterial gene. - Silva, C L (1993)
When the immunodominant 65,000 MW heat-shock protein of Mycobacterium leprae (ML65hsp) was expressed from the transfected mycobacterial gene in the mouse macrophage cell line J774.G8, the antigen was recognized by specifically sensitized CD4+ splenocytes in association with major histocompatibility complex (MHC) class II and CD4. Inhibition by monensin, leupeptin and chloroquine but not brefeldin A indicated dependence of presentation upon endosomal antigen processing. Although direct access of the endogenously synthesized antigen to the endosomal pathway of presentation, without extracellular release followed by endocytosis, could not be discounted, antigen was present in supernatants of the transfected cells in a form that could be presented by fixed macrophages and a form that required further processing for presentation. Each of three monoclonal antibodies (mAb) specific for widely separated linear amino acid epitopes of the antigen strongly inhibited recognition, suggesting steric interference with antigen-presenting cell (APC)-T cell interaction. Tests with splenocytes from vaccinated congenic mice indicated that recognition was not restricted by MHC haplotype. The significance and mechanism of this apparent MHC context-independent interaction of the presented antigen with specific T-cell receptor (TcR) remain to be explored.